2012
DOI: 10.1364/boe.3.001793
|View full text |Cite
|
Sign up to set email alerts
|

Light scattering from edematous human corneal grafts’ microstructure: experimental study and electromagnetic modelization

Abstract: Along with the lens, the cornea is the only transparent tissue in the human body. However, the development of an edema involves structural disturbances increasing light scattering and leading to the opacification of the cornea. Several mechanisms of transparency loss have been studied in the literature, but the whole phenomenon is complex and the part played by each scatterer is still unclear. We propose here to study human corneal grafts combining microscopic OCT imagery with far-field measurement of the scat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…Matrix changes also occur but these contribute less to the observed light scatter. A similar effect occurs in corneal oedema (bullous keratopathy, Fuch's dystrophy) but in this case there are local decreases in refractive index caused by pooling of fluid into so-called “lakes” ( Casadessus et al., 2012 ) ( Fig. 8 ).…”
Section: Causes Of Light Scatter In Corneal Pathologiesmentioning
confidence: 86%
“…Matrix changes also occur but these contribute less to the observed light scatter. A similar effect occurs in corneal oedema (bullous keratopathy, Fuch's dystrophy) but in this case there are local decreases in refractive index caused by pooling of fluid into so-called “lakes” ( Casadessus et al., 2012 ) ( Fig. 8 ).…”
Section: Causes Of Light Scatter In Corneal Pathologiesmentioning
confidence: 86%
“…We will assume throughout this study that the hydration of the SC results in a thickness increase of the corneocytes, which has already been established . A quick comparison between SC and eye cornea shows that cornea hydration increases the opacity of the cornea by increasing its thickness .…”
Section: Introductionmentioning
confidence: 89%
“…15,16 An increase in light scattering and optical dispersion can lead to corneal opacification and impaired vision due to loss of transparency. 1,17,18 Although the causes of increased optical dispersion may vary, many studies of dystrophy-affected opaque corneas show alterations in the supraorganization of the fibrils. 17,[19][20][21][22] Moreover, Chakravarti et al 23,24 demonstrated that in mice with a null mutation in the gene encoding the proteoglycan lumican, which regulates type I collagen fibrillogenesis, congenital corneal opacities are associated with changes in fibrillar thickness and the paths of collagen fibers within the stroma.…”
Section: Introductionmentioning
confidence: 99%
“…An increase in light scattering and optical dispersion can lead to corneal opacification and impaired vision due to loss of transparency 1,17,18 . Although the causes of increased optical dispersion may vary, many studies of dystrophy‐affected opaque corneas show alterations in the supraorganization of the fibrils 17,19–22 .…”
Section: Introductionmentioning
confidence: 99%